2009
DOI: 10.1128/aac.00418-09
|View full text |Cite
|
Sign up to set email alerts
|

Besifloxacin, a Novel Fluoroquinolone, Has Broad-Spectrum In Vitro Activity against Aerobic and Anaerobic Bacteria

Abstract: The antibacterial spectrum of besifloxacin, a novel fluoroquinolone recently approved for treatment of ocular infections, was studied using 2,690 clinical isolates representing 40 species. Overall, besifloxacin was the most potent agent tested against gram-positive pathogens and anaerobes and was generally equivalent to comparator fluoroquinolones in activity against most gram-negative pathogens. Besifloxacin demonstrated potent, broad-spectrum activity, which was particularly notable against gram-positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 14 publications
5
84
1
1
Order By: Relevance
“…In comparison, ciprofloxacin resistance was observed in a much smaller proportion of methicillin-sensitive S. aureus and S. epidermidis strains (9% and 15%, respectively). In agreement with previous studies, 6,31,32,41 besifloxacin demonstrated potent in vitro activity against methicillin-resistant staphylococcal isolates, with MIC 90 values against CipR-MRSA and CipR-MRSE at least eight-to 128-fold lower than that of other fluoroquinolones and comparable to that reported for vancomycin in recent surveillance studies (1-2 µg/mL). …”
supporting
confidence: 77%
See 2 more Smart Citations
“…In comparison, ciprofloxacin resistance was observed in a much smaller proportion of methicillin-sensitive S. aureus and S. epidermidis strains (9% and 15%, respectively). In agreement with previous studies, 6,31,32,41 besifloxacin demonstrated potent in vitro activity against methicillin-resistant staphylococcal isolates, with MIC 90 values against CipR-MRSA and CipR-MRSE at least eight-to 128-fold lower than that of other fluoroquinolones and comparable to that reported for vancomycin in recent surveillance studies (1-2 µg/mL). …”
supporting
confidence: 77%
“…28,29 Many of these methicillin-resistant strains showed concurrent resistance to other non-β-lactam antibiotics, including aminoglycosides, macrolides, tetracyclines, and/or fluoroquinolones, making the treatment of ocular infections caused by these pathogens a challenge. [24][25][26][27][28][29][30][31][32][33] Although conjunctivitis infections with methicillin-resistant staphylococci are generally not vision-threatening, 24 potentially catastrophic complications have been reported with other ocular infections involving such organisms (eg, keratitis, cellulitis, endophthalmitis). [34][35][36] Topical fluoroquinolones are often used in the treatment of bacterial conjunctivitis due to their low toxicity, broad spectrum of activity, and bactericidal activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing resistance of S. aureus to many drug classes, including fluoroquinolones, has resulted in the emergence of multidrug-resistant strains, emphasizing the need for new antimicrobial agents. Besifloxacin is a novel 7-azepinyl-8-chloro-fluoroquinolone that has shown improved in vitropotency as well as clinical efficacy against numerous ophthalmic pathogens [1,2,3,4]. It has recently been approved in the United States as besifloxacin ophthalmic suspension, 0.6% (Besivance®) for the topical treatment of bacterial conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/075325 doi: bioRxiv preprint first posted online Sep. 15, 2016; bioactivity. The secreted levels of benzylpenicillin are similar to those required for antibiotic action against various bacteria such as Streptococcus pyogenes 19 . Therefore, to test the bioactivity of the secreted benzylpenicillin, we diluted liquid cultures of S. pyogenes with spent culture media from either Sc.P2 or from an inactivated version of Sc.P2 (Sc.P2x) that does not produce benzylpenicillin (Fig 3a).…”
Section: Antibiotic Action Of the Spent Yeast Culture Mediamentioning
confidence: 67%